Social emergence : societies as complex systems - Sawyer, Robert Keith, 1960- (Cambridge : Cambridge university press, 2005)
Sociologists have long believed that psychology alone can't explain what happens when people work together in complex modern societies. In contrast, most psychologists and economists believe that we can explain much about social life with an accurate theory of how individuals make choices and act on them. R. Keith Sawyer argues, however, that societies are complex dynamical systems, and that the best way to resolve these debates is by developing the concept of emergence, paying attention to multiple levels of analysis--individuals, interactions, and groups--with a dynamic focus on how social group phenomena emerge from communication processes among individual members.
Emergence, complexity, and social science -- The third wave of social systems theory -- The history of emergence -- Emergence in psychology -- Emergence in sociology -- Durkheim's theory of social emergence -- Emergence and elisionism -- Simulating social emergence with artificial societies -- Communication and improvisation -- The emergence paradigm.
Includes bibliographical references (p. 231-259) and index.
Keywords: Communication -- Social aspects; Social evolution; Social systems; Sociology